Compliance to traditional birth practices and poor perception of formal health facility: exploring actions to social determinants of health and barriers to care access in indigenous “Suku Anak Dalam“ community - Inriyani Takesan; Musa Musa; Retna Siwi Padmawati; Mubasysyir Hasanbasri; Mohammad Hakimi (Berita Kedokteran Masyarakat (BKM), 2018)
People living in isolated communities are vulnerable to suffering from illness because of their lack of access to available known effective treatment in health facilities around them, including in maternal and child issues. The goal of this in-depth interview and one month-direct observation living in the community is to explore the belief and available structure of local health-seeking behavior among the Suku Anak Dalam community. Our findings suggest that the community has its own traditional belief that explains their birth practices. Interpretation of concepts such as anak peranakan, taputangan, pekarom, and delom system are unique and inseparable from the interpretation of their ideal life and their trust in God. In the other side, their poor perception about public health facilities is influenced by their experience dealing with formal health facilities. When a community gets what they perceived as poor services, they will not believe and do not come back to seek help from formal health facilities. Our study confirmed that the cultural explanation of birth and belief related to traditional birth delivery services remain existent and practiced, which limits access to a government health facility. If the community is free to choose alternative care outside their traditional system, people may obtain effective treatments from the surrounding health facilities. SAD women feel comfortable with their cultural practices. They have a negative perception and feel uncomfortable about formal health facilities showed inadequate government efforts to bring services to a specific social group. Health workers in isolated areas with traditional belief should be prepared and paid under a contract basis, different from the regular workers. They need to improve the communication skills that allow them to engage with people from different cultures. They need to work with officers from other sectors, both in formal and informal settings.